HUBUNGAN PERSONAL HYGINE DENGAN KEJADIAN KEPUTIHAN PADA REMAJAPUTRI KELAS VIII DI MTsN NGEMPLAK, SLEMAN, YOGYAKARTA TAHUN 2016 - Mei Munawwarah (Jurnal Kesehatan Husada Gemilang, 2018)
Flour albus is an abnormal fluid discharge from vagina, smelling or not with local itchiness. In Indonesia, about 90% women are potentially undergoing the flour albus because Indonesia is a tropical country, so fungi can easily grow that results many of flour albus cases on Indonesian women. The purpose of this research was to identify and clarify the correlation among personal hygiene, knowledge, attitude, nutritional status, stress level, teacher supports, family supports, friends’ supports and flour albus existence on teenage female students of VIII grade in MTsN Ngemplak, Sleman, Yogyakarta, in year of 2016. This research used case control approach. There were 40 pupils for flour albus and 40 pupils for control group (students with no flour albus). The analysis were univariate, bivariate, and multivariate with multiple logistic regression.The Result of the analysis showed that personal hygiene there was no significant correlation with fluor albus existence. The factors however which are related to the flour albus existence involve the stress level, knowledge, attitude, and teacher supports. The factors which are not related to personal hygiene that are family supports, friends’ support and nutrition status. The flour albus probability is 33,5%. Accordingly, MTsN Ngemplak Yogyakarta is expected to improve and advance the students’ knowledge through biology subject or direct counseling done by teachers, and to have leaflets for knowledge improvement.